Islamic Religious Education for Children in Javanese Family: A Study of Ethno Phenomenology - Rochmah, Elfi Yuliani; Chaer, Moh. Toriqul; Suud, Fitriah M.; Sukatin, Sukatin (IAIN Ponorogo, 2021)
This study aims to determine the Islamic religious education of children within Javanese families in Krajan Hamlet, Jogorogo District, Ngawi Regency, East Java, Indonesia. This study employed an ethno phenomenological approach. It focuses on the ethnographer's work model using a phenomenological approach to deeply understand cultural and religious experiences. The data collection techniques used were in depth interviews, participant observation, literature study, documentation, and active listening, all of which contributed to obtaining rich and comprehensive data. The findings reveal that Javanese families uphold the cultural philosophy of narima ing pandhum—an attitude of accepting destiny with sincerity and gratitude—as a foundational moral principle, aiming to prevent negative thoughts, feelings, and behaviors. The core educational content centers on ‘Aqidah (creed), Ibadah (worship), and Akhlaq (morality), taught through habituation, advice, and role modeling by parents and elders. Furthermore, the study highlights how Javanese identity is shaped from early childhood by cultivating communal values such as mutual assistance, empathy, generosity, and simplicity, which are consistently reinforced and passed down across generations.